Influence of adding nano-graphite powders on the microstructure and gas hydrogen storage properties of ball-milled Mg90Al10 alloys. (August 2019) - Shang, Hongwei; Li, Yaqin; Zhang, Yanghuan; Wei, Xin; Qi, Yan; Zhao, Dongliang
Abstract: A small quantity of nano-graphite powders were introduced into the Mg90 Al10 alloy to obtain the ball milled Mg90 Al10 + x wt% graphite ( x = 0, 1, 3, 5 and 8) composites. The influences of adding nano-graphite powders on the microstructure and hydrogen storage performances were studied. The microstructure analysis showed that adding nano-graphite powders not only promotes the formation of Mg17 Al12 phase, but also increases the number of Al atoms that enter into the crystal lattice of Mg. The performance test indicated that adding nano-graphite powders can improve the activation performance and enhance the hydrogenation/dehydrogenation kinetics and capacity. It also is benificial to lower the thermodynamic stability of the hydride. The dehydrogenation enthalpy (Δ H de ) and activation energy ( E de (a)) decrease at different degrees after adding nano-graphite powders. Dehydrogenation enthalpy of the composites is 75.43, 74.63, 73.20, 72.68 and 71.52 kJ mol −1 H2 when the value of x is 0, 1, 3, 5 and 8, respectively. Dehydrogenation activation energy of the composites is 162.06, 161.26, 159.07, 156.15 and 158.26 kJ mol −1 H2 when the value of x is 0, 1, 3, 5 and 8, respectively. Graphical abstract: Image 1